2020
DOI: 10.1039/d0en00095g
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the dietary bioavailability of copper sulphate and copper oxide nanomaterials inex vivogut sacs of rainbow trout: effects of low pH and amino acids in the lumen

Abstract: Diet is an important exposure pathway of engineered nanomaterials (ENMs) in fish, but the long duration of in vivo toxicity tests is a barrier to hazard assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…This was likely caused by increased dissolution of the CuO ENMs in the gut lumen in the presence of cysteine, and transport of Cu-cysteine into the tissue via dissolved Cu uptake pathways. 19 Together, these data supported the hypothesis that intact nanoscale particulates of Cu are too large for uptake on solute transporters [see discussion Handy et al;20 as demonstrated for silver (Ag) ENMs 21 ], but also demonstrate that the chemical composition of gut lumen can drive the transformations of metallic ENMs and subsequent total Cu uptake. 19 Notably, the bioaccumulation potential of the CuSO 4 and CuO ENMs in fish has been shown using the ex vivo gut sac technique.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…This was likely caused by increased dissolution of the CuO ENMs in the gut lumen in the presence of cysteine, and transport of Cu-cysteine into the tissue via dissolved Cu uptake pathways. 19 Together, these data supported the hypothesis that intact nanoscale particulates of Cu are too large for uptake on solute transporters [see discussion Handy et al;20 as demonstrated for silver (Ag) ENMs 21 ], but also demonstrate that the chemical composition of gut lumen can drive the transformations of metallic ENMs and subsequent total Cu uptake. 19 Notably, the bioaccumulation potential of the CuSO 4 and CuO ENMs in fish has been shown using the ex vivo gut sac technique.…”
Section: Introductionsupporting
confidence: 66%
“…19 Together, these data supported the hypothesis that intact nanoscale particulates of Cu are too large for uptake on solute transporters [see discussion Handy et al;20 as demonstrated for silver (Ag) ENMs 21 ], but also demonstrate that the chemical composition of gut lumen can drive the transformations of metallic ENMs and subsequent total Cu uptake. 19 Notably, the bioaccumulation potential of the CuSO 4 and CuO ENMs in fish has been shown using the ex vivo gut sac technique. 19 In as little as 4 hours, total Cu from both materials accumulated in the mucosa of the gastrointestinal tract of rainbow trout, with the highest concentrations in the mid and hind intestines.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…There are only a few studies assessing dietary uptake of nanoparticulate Cu in fish, and findings concerning the intestinal absorption efficiency and accumulation in inner tissues compared to dissolved Cu species vary. [34][35][36] Some information on NP transfer from invertebrate prey organisms to fish can be inferred from studies that examined intestinal uptake and accumulation of metalIJoxide) NPs from spiked artificial diets. [37][38][39][40][41][42][43][44][45] Altogether, the data from the few studies published on dietary exposure of fish to Cu(O) NPs suggest that Cu from NP-spiked diet is available, but uptake is limited compared to dissolved Cu.…”
Section: Introductionmentioning
confidence: 99%